Hubungan Besar Keluarga, Pendapatan Keluarga dan Peran Tenaga Kesehatan dengan Penerapan Kadarzi di Wilayah Kerja Puskesmas Pondok Tinggi - Citra Ratu Fanesha; Djayusmantoko Djayusmantoko; Merita Merita; Andicha Gustra Jeki (3031-8572, 2022)
Nutritional problems in Indonesia are still high, the main cause is the low public awareness of efforts to improve nutrition. The period of the first 2 years of life is a critical period because at this time there is very rapid growth and development. The presence of nutritional disorders at this time is permanent and cannot be reversed even though nutritional needs can be met in the next period of life. The design of this research is quantitative with a cross sectional, the research sample is 81 families taken by proportional sampling technique. Data was collected by direct interviews with respondents using a questionnaire about Kadarzi, observing KMS books. Data analysis includes univariate analysis, bivariate analysis with chi-square. Aunivariate analysis of most of the respondents had families with small categories (70.4%), high incomes (59.3%), active health workers (69.1%), and families who had low levels of energy (61.7%). The chi-squere test shows that there is a relationship between family size and the application of KADARZI (0.002), there is a relationship between family income and the application of KADARZI (0.001), there is a relationship between the role of health workers and the application of KADARZI (0.001).It can be concluded that there is a significant relationship between family size, family income, and the role of health workers in the application of KADARZI.